2019
DOI: 10.1111/jcmm.14571
|View full text |Cite
|
Sign up to set email alerts
|

ST2 blockade mitigates peritoneal fibrosis induced by TGF‐β and high glucose

Abstract: Peritoneal fibrosis (PF) is an intractable complication of peritoneal dialysis (PD) that leads to peritoneal membrane failure. This study investigated the role of suppression of tumorigenicity (ST)2 in PF using patient samples along with mouse and cell‐based models. Baseline dialysate soluble (s)ST2 level in patients measured 1 month after PD initiation was 2063.4 ± 2457.8 pg/mL; patients who switched to haemodialysis had elevated sST2 levels in peritoneal effluent (1576.2 ± 199.9 pg/mL, P = .03), which was as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…TGF-β1 regulates cell physiology, proliferation, and differentiation and plays a critical role in the pathogenesis and development of various diseases [5]. Previous studies indicated that TGF-β1 is a novel profibrotic factor that enhances the expression of profibrotic genes through a novel signaling cascade [4, 5]. It has been reported that blocking the TGF-β1 signaling pathway could significantly attenuate angiogenesis and peritoneal fibrosis in PD mouse models [29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TGF-β1 regulates cell physiology, proliferation, and differentiation and plays a critical role in the pathogenesis and development of various diseases [5]. Previous studies indicated that TGF-β1 is a novel profibrotic factor that enhances the expression of profibrotic genes through a novel signaling cascade [4, 5]. It has been reported that blocking the TGF-β1 signaling pathway could significantly attenuate angiogenesis and peritoneal fibrosis in PD mouse models [29].…”
Section: Discussionmentioning
confidence: 99%
“…PD-related peritoneal fibrosis is identical to EMT of peritoneal mesothelial cells, and the loss of peritoneal membrane function results in UF failure. PD solution induces peritoneal irritation, which promotes peritoneal mesothelial cells to translation into a mesenchymal phenotype, including the downregulation of epithelial markers such as E-cadherin and the upregulation of mesenchymal protein expression, such as N-cadherin, vimentin, and α-SMA, a process mediated by TGF-β1 [4]. EMT usually refers to a switch of E- to N-cadherin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effluent from clinically stable patients was obtained and immediately processed 18 . Bags were suspended for 3–4 h in an incubator at 37°C to allow the cells to settle at the bottom.…”
Section: Methodsmentioning
confidence: 99%
“…Wang et al, 2018b) (Morinelli et al, 2016). Currently, only a few treatments, such as metformin and tamoxifen, or genetic approaches such as gene knockout, have shown to inhibit EMT in vivo or in vitro in an effective way (Shin et al, 2017) (Chul et al, 2019) (Yan et al, 2018). Therefore, an urgent need remains for an effective clinical treatment of PD-associated peritoneal fibrosis.…”
Section: Introductionmentioning
confidence: 99%